(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
Argentine Patagonia was incorporated to the national State late in the last decades of the 19th century, after the end of the bloody military campaign that sought state control of the indigenous territory of the south. From then until the 1930s the process of providing educational institutions to the vast Patagonian territory was discontinuous, slow and very uneven in the different regional spaces, intensifying in the urban nuclei and becoming invisible in the Patagonian mesetaria zone. In this context, it is the purpose of this paper to analyze the trajectories of female students and teachers in the first half of the 20th century from the perspective of those who exercised direct authority over them: principals -mostly males- and school inspectors. We are interested in analyzing, from a gender perspective, the presence of teachers in the classrooms, the desired behaviors and the goals to be met according to pedagogical and axiological considerations, within the framework of a normalizing and prescriptive process. For this purpose, we have used a vast array of sourcesreferring to the National Territory of Rio Negro, including school historical books, inspection reports, school concepts teachers, school visit books, school reports, regional and national press articles.